BEHAVIOR OF ACOUSTIC-GRAVITATIONAL WAVES IN THE MESOSPHERE OVER THE KAZAKHSTAN REGION - Somsikov, V.M.; Andreev, A.B.; Kapytin, V.I.; Mukasheva, S.N. (Academic Scientific Journal of Computer Science, 2020)
Kazakhstan has been going on for more than 10 years carried out studies I effects in the mesosphere at the basis of modern optical spectrometer SATI (Spectral airglow the Temperature Imager), which is mounted on a mountain complex of Ionosphere Institute - radiopoligone «Orbita» at an altitude of 2730 m above sea level [43 ° 03'30 '' N , 76 ° 58'24 '' E]. The results of a continuous series of optical spectrometric observations of variations in the mesosphere between 2010 and 2016. Observations were made in Kazakhstan on the basis of modern optical spectrometer SATI (Spectral airglow Temperature Imager), which is mounted on a mountain complex of Ionosphere Institute - radiopoligone "Orbita" at an altitude of 2730 m above sea level [43 ° 03'30 ''N , 76° 58'24 ''E]. The spectral analysis of recorded wave disturbances over the entire observation period showed a wavelength distribution characteristic of acoustic-gravitational waves. It has been established that the maximum number of recorded disturbances in the mesosphere is about 100-200 km long, a noticeable separate peak is observed for wavelengths of about 350-400 km. The directions of propagation of acoustic-gravitational waves have a seasonal dependence. The western maximum in the distribution directions is observed in all seasons. The south-south-western maximum is observed mainly in winter and autumn. East-north-east has a maximum value in the spring-summer months.